(Bi, Pb)-2223 superconducting thin film and preparation method and application thereof
By using 2,4,6-trimethylbenzoyl-diphenylphosphine oxide as a photoinitiator in the preparation of (Bi,Pb)-2223 superconducting films, combined with the Sol-Gel method and the free radical polymerization method, the problems of high cost, complex operation and poor accuracy of preparing fine pattern superconducting films in the prior art are solved, and efficient and low-cost fine pattern preparation is achieved, and good superconducting performance is maintained.
Patent Information
- Application Number
- CN202510329637.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, when preparing (Bi, Pb)-2223 superconducting films with fine patterns, the cost is high, the operation is complex, the etching rate is low, and the ultraviolet absorption rate of the photosensitive sol-gel lithography method is low, resulting in poor accuracy and low efficiency.
2,4,6-trimethylbenzoyl-diphenylphosphine oxide was used as the photoinitiator, combined with the Sol-Gel method and the free radical polymerization method, the ultraviolet photosensitive characteristics of the gel film were improved, and a fine pattern (Bi,Pb)-2223 superconducting film with high precision was prepared by ultraviolet radiation and polar solvent washing.
The accuracy and efficiency of lithographic pattern preparation are improved. The prepared (Bi,Pb)-2223 superconducting film has good micro pattern morphology, low cost, and good superconducting performance.
Smart Images

Figure CN119920537A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micro-processing methods for superconducting thin film materials, and specifically relates to a (Bi, Pb)-2223 superconducting thin film and a preparation method and application thereof. Background Art
[0002] High-temperature superconducting films have many unique properties, such as high critical temperature and high critical current density, which make them have broad application prospects in power transmission, magnetic levitation trains, medical imaging and other fields. However, to realize these applications, it is necessary to prepare superconducting films with fine patterns to meet the requirements of different devices for material properties and structures. Therefore, fine pattern preparation technology is one of the keys to promote the expansion of high-temperature superconducting film applications.
[0003] (Bi,Pb)-2223 superconducting film is a superconducting film with a high transition temperature (110K) and its own intrinsic Josephson effect. Therefore, it has attracted widespread attention and is often prepared as a superconducting film for use in superconducting devices.
[0004] At present, the traditional processing method for preparing (Bi, Pb)-2223 superconducting films with fine patterns is mainly photolithography, but this method is costly, complicated to operate, and has a low etching rate, so it cannot be widely used. Photosensitive sol-gel photolithography is a new type of superconducting film fine pattern processing method, which specifically uses photosensitive metal chelates to directly give ultraviolet photosensitivity to the gel film containing the metal element of the target material, and then obtains the target metal oxide through ultraviolet mask exposure, dissolution, heat treatment and other steps. Compared with the above-mentioned traditional photolithography, photosensitive sol-gel photolithography does not require subsequent wet or dry etching steps, is simple to operate, and has improved photosensitivity efficiency. However, the ultraviolet absorption band of the currently commonly used photosensitive metal chelates (β-diketone metal chelates) is usually in the range of 300 to 330nm, which is not well matched with the emission wavelength of existing UV mercury lamps and UV-LED lamps, and the ultraviolet light absorption rate is low, resulting in poor precision and low efficiency of fine patterns prepared by photosensitive sol-gel photolithography. Summary of the invention
[0005] The purpose of the present invention is to provide a (Bi, Pb)-2223 superconducting film and a preparation method and application thereof. The preparation method provided by the present invention can improve the ultraviolet photosensitivity of the gel film, enhance the accuracy and efficiency of photolithography pattern preparation, and the prepared (Bi, Pb)-2223 superconducting film has a fine pattern morphology with good precision, low cost, and the (Bi, Pb)-2223 superconducting film can maintain good superconducting performance.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a (Bi, Pb)-2223 superconducting film, comprising the following steps:
[0008] Bismuth salt, lead salt, strontium salt, calcium salt, copper salt, organic complexing agent, photoinitiator and alcohol solvent are mixed to obtain (Bi, Pb)-2223 photosensitive sol; the (Bi, Pb)-2223 photosensitive sol includes bismuth coordination compound; the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the organic complexing agent includes at least one of organic olefin acid complexing agent and β-diketone complexing agent;
[0009] The (Bi, Pb)-2223 photosensitive sol is formed into a film on the surface of a substrate by spin coating to obtain a (Bi, Pb)-2223 gel film;
[0010] The (Bi, Pb)-2223 gel film is irradiated with light under ultraviolet light through a mask plate with a specific pattern, and then washed with a polar solvent composed of methanol and acrylic acid, so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the substrate, and obtaining a (Bi, Pb)-2223 gel film with fine patterns; the wavelength of the ultraviolet light used for the light irradiation is 260 to 430 nm; in the polar solvent, the volume ratio of methanol to acrylic acid is 7:1; the structure of the fine pattern is a microbridge structure with a width of 10 μm;
[0011] The (Bi, Pb)-2223 gel film with fine patterns is subjected to heat treatment to obtain the (Bi, Pb)-2223 superconducting film on the surface of the substrate.
[0012] Preferably, the thickness of the (Bi, Pb)-2223 gel film is 200 nm.
[0013] Preferably, the wavelength of the ultraviolet light used for the light irradiation is 260 to 430 nm; and the time of the light irradiation is 45 to 60 min.
[0014] Preferably, the heat treatment includes a first heat treatment, a second heat treatment and a third heat treatment performed sequentially;
[0015] The first heat treatment is performed in a nitrogen atmosphere; the temperature of the first heat treatment is 100-150° C., the holding time is 20 min, and the heating rate to the temperature of the first heat treatment is 4-10° C. / min;
[0016] The second heat treatment is performed in a mixed gas atmosphere including water vapor, oxygen and nitrogen; during the second heat treatment, the volume ratio of water vapor, oxygen and nitrogen is 10:5:85; the temperature of the second heat treatment is 550-600°C, the holding time is 30-90min, and the heating rate from the temperature of the first heat treatment to the temperature of the second heat treatment is 10-20°C / min;
[0017] The third heat treatment is carried out in a mixed gas atmosphere including water vapor, oxygen and nitrogen; during the third heat treatment, the volume ratio of water vapor, oxygen and nitrogen is 10:5:85; the temperature of the third heat treatment is 830-880°C, the insulation time is 60-180min, and the heating rate from the temperature of the second heat treatment to the temperature of the third heat treatment is 8-20°C / min.
[0018] Preferably, the mixing comprises the following steps:
[0019] The bismuth salt, the first part of the organic complexing agent and the alcohol solvent are first mixed in a molar ratio of 1:12-30:20-30 to obtain a bismuth solution;
[0020] The lead salt, the second part of the organic complexing agent and the alcohol solvent are mixed in a molar ratio of 1:10 to 20:15 to 25 to obtain a lead solution;
[0021] The strontium salt, the third part of the organic complexing agent and the alcohol solvent are mixed in a molar ratio of 1:15-30:20-30 to obtain a strontium solution;
[0022] The calcium salt, the fourth part of the organic complexing agent and the alcohol solvent are mixed in a molar ratio of 1:15-30:20-30 to obtain a calcium solution;
[0023] The copper salt, the remaining organic complexing agent and the alcohol solvent are mixed in a molar ratio of 1:6 to 10:30 to 80 to obtain a copper solution;
[0024] The bismuth solution, the lead solution, the strontium solution, the calcium solution and the copper solution are mixed for the sixth time and then mixed with the photoinitiator for the seventh time.
[0025] Preferably, the (Bi, Pb)-2223 photosensitive sol includes bismuth ions, lead ions, strontium ions, calcium ions and copper ions; the molar ratio of the bismuth ions, lead ions, strontium ions, calcium ions and copper ions is 1.9:0.3:2:2:3.
[0026] Preferably, the molar ratio of the photoinitiator to the bismuth ion is 1:4-10.
[0027] Preferably, the organic olefinic acid complexing agent includes acrylic acid or α-methacrylic acid; and the β-diketone complexing agent includes benzoyl acetone.
[0028] The present invention provides a (Bi, Pb)-2223 superconducting film obtained by the preparation method described in the above technical solution.
[0029] The present invention provides the application of the (Bi, Pb)-2223 superconducting film described in the above technical solution in superconducting devices.
[0030] The invention provides a method for preparing a (Bi, Pb)-2223 superconducting film, comprising the following steps: mixing bismuth salt, lead salt, strontium salt, calcium salt, copper salt, organic complexing agent, photoinitiator and alcohol solvent to obtain a (Bi, Pb)-2223 photosensitive sol; the (Bi, Pb)-2223 photosensitive sol comprises a bismuth coordination compound; the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the organic complexing agent comprises at least one of an organic olefin acid complexing agent and a β-diketone complexing agent; forming a film of the (Bi, Pb)-2223 photosensitive sol on a substrate surface to obtain a (Bi, Pb)-2223 gel film; subjecting the (Bi, Pb)-2223 photosensitive sol to ultraviolet light through a mask plate with a specific pattern. The gel film is subjected to light irradiation, and then washed with a polar solvent composed of methanol and acrylic acid, so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the substrate, and obtaining a (Bi, Pb)-2223 gel film with fine patterns; the wavelength of the ultraviolet light used for the light irradiation is 260-430nm; in the polar solvent, the volume ratio of methanol to acrylic acid is 7:1; the structure of the fine pattern is a microbridge structure with a width of 10μm; the (Bi, Pb)-2223 gel film with fine patterns is heat-treated to obtain the (Bi, Pb)-2223 superconducting film on the surface of the substrate. The present invention adopts 2,4,6-trimethylbenzoyl-diphenylphosphine oxide as a photoinitiator for preparing a superconducting film with fine patterns for the first time. Under the condition of ultraviolet light irradiation, an organic complexing agent can combine with free radicals generated by 2,4,6-trimethylbenzoyl-diphenylphosphine oxide to generate a stable macromolecular network structure, thereby causing the ultraviolet absorption peak to red-shift to the range of 350 to 400 nm, better matching the i-line wavelength commonly used by UV mercury lamps or the 365 nm band commonly used by UV-LED lamps, greatly reducing the exposure time, improving the ultraviolet photosensitivity of the (Bi, Pb)-2223 superconducting film, and improving the preparation accuracy and preparation efficiency of the photolithography patterns.
[0031] Furthermore, the heat treatment of the present invention can, on the one hand, reduce the thickness of the (Bi, Pb)-2223 superconducting film from 200 nm to 150 nm; on the other hand, the heat treatment can promote the phase formation of (Bi, Pb)-2223, as follows: within the heat treatment temperature range of 600 to 700°C, Sr2CuO3 and Bi2O3 react to form Bi-2201 phase; during the heat treatment process of 700 to 800°C, Ca2PbO4, CuO and Bi-2201 phase react to form (Bi, Pb)-2212 phase; as the temperature continues to rise to 840 to 860°C, the (Bi, Pb)-2212 phase will react with Ca2CuO3 and CuO to form a (Bi, Pb)-2223 high-temperature superconducting phase.
[0032] The preparation method of the present invention can improve the ultraviolet photosensitivity of the gel film, enhance the accuracy and efficiency of photolithography pattern preparation, and the obtained (Bi, Pb)-2223 superconducting film has a fine pattern morphology with good precision. The present invention adopts a combination of the Sol-Gel method and the free radical polymerization method to realize the preparation of the (Bi, Pb)-2223 superconducting film with fine patterns, reduces the time of ultraviolet exposure (from the traditional 80 to 100 minutes to the current 20 to 60 minutes), and effectively improves the exposure efficiency; on this basis, heat treatment is performed to obtain a (Bi, Pb)-2223 superconducting film with good fine pattern morphology. The preparation method provided by the present invention is simple to operate, low in cost, high in preparation efficiency, and good in accuracy. While obtaining fine patterns, it will not affect the generation of the (Bi, Pb)-2223 phase and can maintain good superconducting performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0034] Figure 1 The preparation flow chart of fine patterned (Bi, Pb)-2223 superconducting thin film;
[0035] Figure 2 This is a confocal plane topography image of the (Bi, Pb)-2223 superconducting film obtained in Example 1;
[0036] Figure 3 This is a confocal three-dimensional morphology image of the (Bi, Pb)-2223 superconducting film obtained in Example 1;
[0037] Figure 4The ultraviolet absorption spectrum of (Bi,Pb)-2223 photosensitive sol obtained by adding 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0038] Figure 5 This is the XRD pattern of the (Bi, Pb)-2223 superconducting film obtained in Example 1;
[0039] Figure 6 RT diagram of the (Bi, Pb)-2223 superconducting film obtained in Example 1;
[0040] Figure 7 is the XRD pattern of the superconducting film obtained in Comparative Example 1;
[0041] Figure 8 The morphology of the (Bi, Pb)-2223 gel film with fine patterns obtained by adding the photoinitiator TPO and irradiating it under ultraviolet light for 25 minutes;
[0042] Fig. 9 The morphology of the (Bi, Pb)-2223 gel film with fine patterns obtained by adding the photoinitiator TPO and irradiating it under ultraviolet light for 35 minutes;
[0043] Fig.10 This is the morphology of the (Bi, Pb)-2223 gel film with fine patterns obtained by adding photoinitiator TPO and irradiating it under ultraviolet light for 45 minutes. DETAILED DESCRIPTION
[0044] The present invention provides a method for preparing a (Bi, Pb)-2223 superconducting film, comprising the following steps:
[0045] Bismuth salt, lead salt, strontium salt, calcium salt, copper salt, organic complexing agent, photoinitiator and alcohol solvent are mixed to obtain (Bi, Pb)-2223 photosensitive sol; the (Bi, Pb)-2223 photosensitive sol includes bismuth coordination compound; the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the organic complexing agent includes at least one of organic olefin acid complexing agent and β-diketone complexing agent;
[0046] The (Bi, Pb)-2223 photosensitive sol is formed into a film on the surface of a substrate by spin coating to obtain a (Bi, Pb)-2223 gel film;
[0047] The (Bi, Pb)-2223 gel film is irradiated with light under ultraviolet light through a mask plate with a specific pattern, and then washed with a polar solvent composed of methanol and acrylic acid, so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the substrate, and obtaining a (Bi, Pb)-2223 gel film with fine patterns; the wavelength of the ultraviolet light used for the light irradiation is 260 to 430 nm; in the polar solvent, the volume ratio of methanol to acrylic acid is 7:1; the structure of the fine pattern is a microbridge structure with a width of 10 μm;
[0048] The (Bi, Pb)-2223 gel film with fine patterns is subjected to heat treatment to obtain the (Bi, Pb)-2223 superconducting film on the surface of the substrate.
[0049] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0050] The invention mixes bismuth salt, lead salt, strontium salt, calcium salt, copper salt, organic complexing agent, photoinitiator and alcohol solvent to obtain (Bi, Pb)-2223 photosensitive sol. In the present invention, the mixing includes the following steps: first mixing a bismuth salt, a first part of an organic complexing agent and an alcohol solvent at a molar ratio of 1:12-30:20-30 to obtain a bismuth solution; second mixing a lead salt, a second part of an organic complexing agent and an alcohol solvent at a molar ratio of 1:10-20:15-25 to obtain a lead solution; third mixing a strontium salt, a third part of an organic complexing agent and an alcohol solvent at a molar ratio of 1:15-30:20-30 to obtain a strontium solution; fourth mixing a calcium salt, a fourth part of an organic complexing agent and an alcohol solvent at a molar ratio of 1:15-30:20-30 to obtain a calcium solution; fifth mixing a copper salt, the remaining organic complexing agent and an alcohol solvent at a molar ratio of 1:6-10:30-80 to obtain a copper solution; sixth mixing the bismuth solution, the lead solution, the strontium solution, the calcium solution and the copper solution and then seventh mixing with a photoinitiator.
[0051] In the present invention, the bismuth salt may include bismuth acetate; the lead salt may include lead acetate; the strontium salt may include strontium acetate; the calcium salt may include calcium acetate; and the copper salt may include copper acetate. In the present invention, the organic complexing agent contains an unsaturated bond; the organic complexing agent may include at least one of an organic olefinic acid complexing agent and a β-diketone complexing agent; the organic olefinic acid complexing agent may include acrylic acid or α-methacrylic acid; and the β-diketone complexing agent may include benzoyl acetone. In a specific embodiment of the present invention, the organic complexing agent is acrylic acid. In the present invention, the alcohol solvent may include methanol.
[0052] In the present invention, the molar ratio of the bismuth salt, the first part of the organic complexing agent and the first part of the alcohol solvent can be 1:12-30:20-30; in a specific embodiment of the present invention, the molar ratio of the bismuth salt, the first part of the organic complexing agent and the alcohol solvent is 1:12:20. In the present invention, the bismuth salt, the first part of the organic complexing agent and the alcohol solvent can be mixed according to the molar ratio and stirred to obtain a bismuth solution.
[0053] In the present invention, the molar ratio of the lead salt, the second part of the organic complexing agent and the alcohol solvent can be 1:10-20:15-25; in a specific embodiment of the present invention, the molar ratio of the lead salt, the second part of the organic complexing agent and the alcohol solvent is 1:10:20. In the present invention, the lead salt, the second part of the organic complexing agent and the alcohol solvent can be mixed according to the molar ratio and stirred to obtain a lead solution.
[0054] In the present invention, the molar ratio of the strontium salt, the third part of the organic complexing agent and the alcohol solvent can be 1:15-30:20-30; in a specific embodiment of the present invention, the molar ratio of the strontium salt, the third part of the organic complexing agent and the alcohol solvent is 1:15:20. In the present invention, the strontium salt, the third part of the organic complexing agent and the alcohol solvent can be mixed according to the molar ratio and stirred to obtain a strontium solution.
[0055] In the present invention, the molar ratio of the calcium salt, the fourth part of the organic complexing agent and the alcohol solvent can be 1:15-30:20-30; in a specific embodiment of the present invention, the molar ratio of the calcium salt, the fourth part of the organic complexing agent and the alcohol solvent is 1:15:25. In the present invention, the calcium salt, the fourth part of the organic complexing agent and the alcohol solvent can be mixed according to the molar ratio and stirred to obtain a calcium solution.
[0056] In the present invention, the molar ratio of the copper salt, the remaining organic complexing agent and the alcohol solvent can be 1:6-10:30-80; in a specific embodiment of the present invention, the molar ratio of the copper salt, the remaining organic complexing agent and the alcohol solvent is 1:10:30. In the present invention, the copper salt, the remaining organic complexing agent and the alcohol solvent can be mixed according to the molar ratio and stirred to obtain a copper solution.
[0057] After obtaining bismuth solution, lead solution, strontium solution, calcium solution and copper solution, the present invention mixes the bismuth solution, lead solution, strontium solution, calcium solution and copper solution and then adds a photoinitiator to obtain the (Bi, Pb)-2223 photosensitive sol. In the present invention, the (Bi, Pb)-2223 photosensitive sol includes bismuth ions, lead ions, strontium ions, calcium ions and copper ions; the molar ratio of the bismuth ions, lead ions, strontium ions, calcium ions and copper ions can be 1.9:0.3:2:2:3. In the present invention, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. The molar ratio of the photoinitiator to the bismuth ions of the present invention can be 1:4-10; in a specific embodiment of the present invention, the molar ratio of the photoinitiator to the bismuth ions is 1:4, 1:6, 1:8 or 1:10. After mixing the bismuth solution, the lead solution, the strontium solution, the calcium solution, the copper solution and the photoinitiator, the present invention can stir the obtained liquid at room temperature to obtain a (Bi, Pb)-2223 photosensitive sol. In the present invention, the (Bi, Pb)-2223 photosensitive sol includes a bismuth coordination compound.
[0058] In the present invention, through experiments, Bi:Pb:Sr:Ca:Cu=1.9:0.3:2:2:3 (molar ratio) is the best ratio for preparing (Bi,Pb)-2223 photosensitive sol, wherein Pb replaces a part of Bi element, and Pb has a low melting point, which can effectively reduce the reaction temperature, and also ensure that the final (Bi,Pb)-2223 superconducting film has good superconducting properties.
[0059] After obtaining the (Bi, Pb)-2223 photosensitive sol, the present invention forms a film of the (Bi, Pb)-2223 photosensitive sol on the surface of the substrate by spin coating to obtain a (Bi, Pb)-2223 gel film. In the present invention, the substrate may be a single crystal substrate; the single crystal substrate may include a lanthanum aluminate substrate, a strontium titanate substrate or a magnesium oxide substrate. In a specific embodiment of the present invention, the substrate is a lanthanum aluminate substrate, and the crystal direction of the lanthanum aluminate substrate is (001). In a specific embodiment of the present invention, the (Bi, Pb)-2223 photosensitive sol is coated on the surface of the substrate to obtain a (Bi, Pb)-2223 gel film. In the present invention, the conditions of the spin coating method include: the rotation speed may be 4000 to 4500 r / min, and the time may be 40 to 50 s. In a specific embodiment of the present invention, the conditions of the spin coating method are: the rotation speed is 4500 r / min, and the time is 40 s. After the (Bi, Pb)-2223 photosensitive sol is formed into a film on the surface of the substrate by spin coating, the present invention can dry the obtained material. In the present invention, the drying temperature can be 80-100°C, and the time can be 5-10 minutes. In a specific embodiment of the present invention, the drying temperature is 80°C, 90°C or 100°C; the time is 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes. In the present invention, the thickness of the (Bi, Pb)-2223 gel film can be 200nm.
[0060] After preparing the (Bi, Pb)-2223 gel film on the surface of the substrate, the present invention irradiates the (Bi, Pb)-2223 gel film under ultraviolet light conditions through a mask plate with a specific pattern, and then washes it with a polar solvent composed of methanol and acrylic acid, so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the substrate, and obtaining a (Bi, Pb)-2223 gel film with a fine pattern. The present invention can place a mask plate with a specific pattern on the upper surface of the (Bi, Pb)-2223 gel film, and irradiate the (Bi, Pb)-2223 gel film under ultraviolet light conditions. In the present invention, the wavelength of the ultraviolet light used for the light irradiation is 260-430 nm; in a specific embodiment of the present invention, the wavelength of the ultraviolet light used for the light irradiation can be 300-375 nm. The light intensity of the ultraviolet light used for the light irradiation of the present invention can be 54 mw / cm 2. In the present invention, the light irradiation time can be 45 to 60 minutes; in a specific embodiment of the present invention, the light irradiation time is 45 minutes, 50 minutes, 55 minutes or 60 minutes. In the polar solvent of the present invention, the volume ratio of methanol to acrylic acid is 7:1. In the present invention, the structure of the micro-pattern is a micro-bridge structure with a width of 10 μm.
[0061] In the present invention, with the irradiation of ultraviolet light, the organic matter in the (Bi, Pb)-2223 gel film is decomposed, causing the difference in solubility between the exposed part and the unexposed part in the organic solvent, which is manifested as a photosensitive property. After the ultraviolet light irradiation is completed, the present invention dissolves the obtained material in a polar solvent, wherein the part of the (Bi, Pb)-2223 photosensitive sol irradiated by the ultraviolet light remains on the surface of the substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by the ultraviolet light is washed away by the polar solvent, exposing the substrate, thereby forming the expected fine pattern.
[0062] After obtaining the (Bi, Pb)-2223 gel film with fine patterns, the present invention heat treats the (Bi, Pb)-2223 gel film with fine patterns to obtain the (Bi, Pb)-2223 superconducting film on the surface of the substrate.
[0063] In the present invention, the heat treatment may include a first heat treatment, a second heat treatment, and a third heat treatment performed sequentially.
[0064] In the present invention, the first heat treatment can be carried out in a nitrogen atmosphere; in a specific embodiment of the present invention, the purity of the nitrogen is 99.999%. The temperature of the first heat treatment of the present invention can be 100-150°C, the holding time can be 20 minutes, and the heating rate to the temperature of the first heat treatment can be 4-10°C / min. In a specific embodiment of the present invention, the temperature of the first heat treatment is 125°C, 130°C or 135°C; the holding time is 20 minutes; the heating rate to the temperature of the first heat treatment is 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.
[0065] In the present invention, the second heat treatment can be carried out in a mixed gas atmosphere including water vapor, oxygen and nitrogen. During the second heat treatment of the present invention, the volume ratio of the water vapor, oxygen and nitrogen can be 10:5:85; the purity of the oxygen can be 99.999%, and the purity of the nitrogen can be 99.999%. The temperature of the second heat treatment of the present invention can be 550-600°C, the holding time can be 30-90min, and the heating rate from the temperature of the first heat treatment to the temperature of the second heat treatment can be 10-20°C / min. In a specific embodiment of the present invention, the temperature of the second heat treatment is 550°C, 560°C, 570°C or 580°C; the holding time is 40min, 50min or 60min; the heating rate from the temperature of the first heat treatment to the temperature of the second heat treatment is 10°C / min, 15°C / min, 18°C / min or 20°C / min.
[0066] In the present invention, the third heat treatment can be carried out in a mixed gas atmosphere including water vapor, oxygen and nitrogen. During the third heat treatment of the present invention, the volume ratio of water vapor, oxygen and nitrogen can be 10:5:85; the purity of the oxygen can be 99.999%, and the purity of the nitrogen can be 99.999%. The temperature of the third heat treatment of the present invention can be 830-880°C, the holding time can be 60-180min, and the heating rate from the temperature of the second heat treatment to the temperature of the third heat treatment can be 8-20°C / min. In a specific embodiment of the present invention, the temperature of the third heat treatment is 840°C, 845°C, 850°C, 855°C or 860°C; the holding time is 100min, 110min, 120min, 130min, 140min or 150min; the heating rate from the temperature of the second heat treatment to the temperature of the third heat treatment is 8°C / min, 9°C / min, 12°C / min, 15°C / min, 18°C / min or 20°C / min.
[0067] In the present invention, before heat treatment, a layer of organic gel film is attached to the substrate. After heat treatment, organic matter (such as acrylic acid monomer, polyacrylic acid, ester compounds, metal-organic complexes and a small amount of acetic acid) gradually decomposes and turns into an inorganic oxide film, that is, the required (Bi, Pb)-2223 superconducting film (Bi, Pb)-2223 superconducting film is formed to avoid affecting the superconducting performance. On the one hand, the heat treatment of the present invention can reduce the thickness of the (Bi, Pb)-2223 superconducting film from 200nm to 150nm; on the other hand, the heat treatment can promote the phase formation of (Bi, Pb)-2223, as follows: within the heat treatment temperature range of 600 to 700°C, Sr2CuO3 and Bi2O3 react to form the Bi-2201 phase; during the heat treatment process of 700 to 800°C, Ca2PbO4, CuO and Bi-2201 phase react to form the (Bi, Pb)-2212 phase; as the temperature continues to rise to 840 to 860°C, the (Bi, Pb)-2212 phase will react with Ca2CuO3 and CuO to form the (Bi, Pb)-2223 high-temperature superconducting phase.
[0068] The present invention uses 2,4,6-trimethylbenzoyl-diphenylphosphine oxide as a photoinitiator, and after irradiation with ultraviolet light, an active agent free radical is excited, and forms a photosensitivity-stable macromolecule with an organic complexing agent containing an unsaturated bond, so that the absorption peak of the obtained organic gel film moves to a long wavelength (i.e., red shift) to around 365nm, which is consistent with the main wavelength band of ultraviolet light (240-430nm), thereby reducing the exposure time. The (Bi, Pb-2223) gel film is irradiated with ultraviolet light, so that the solubility of the exposed part and the unexposed part in the polar solvent is different, the exposed part is retained in the polar solvent, and the unexposed part is washed away in the polar solvent, thereby forming the expected fine pattern. The present invention uses free radical active substances, and while not affecting the content and performance of the generated (Bi, Pb-2223) superconducting film, it ensures that the obtained fine pattern is still clear and neat.
[0069] The present invention also provides a (Bi, Pb)-2223 superconducting film obtained by the preparation method described in the above technical solution. In the present invention, the pattern of the (Bi, Pb)-2223 superconducting film is a microbridge shape. In the present invention, the thickness of the (Bi, Pb)-2223 superconducting film can be 150nm and the width is 10μm.
[0070] The present invention also provides the application of the (Bi, Pb)-2223 superconducting film described in the above technical solution in superconducting devices.
[0071] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0072] Figure 1 The preparation flow chart of fine patterned (Bi, Pb)-2223 superconducting thin film;
[0073] The substrate used in the embodiment is a single crystal substrate made of lanthanum aluminate (LaAlO3, usually abbreviated as LAO) with a crystal orientation of (001), referred to as "LAO (001) single crystal substrate";
[0074] The photoinitiator used in the example is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, hereinafter referred to as photoinitiator TPO.
[0075] Example 1
[0076] Under room temperature conditions, bismuth acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:12:20 to obtain a bismuth solution; lead acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:10:20 to obtain a lead solution; strontium acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:15:20 to obtain a strontium solution; calcium acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:15:25 to obtain a calcium solution; copper acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:10:30 to obtain a copper solution.
[0077] The bismuth solution, lead solution, strontium solution, calcium solution and copper solution are stirred and mixed at room temperature, wherein the molar ratio of bismuth ion, lead ion, strontium ion, calcium ion and copper ion is 1.9:0.3:2:2:3, to obtain (Bi,Pb)-2223 sol. Photoinitiator TPO (the molar ratio of photoinitiator TPO to bismuth ion is 1:10) is added to the (Bi,Pb)-2223 sol, and stirred at room temperature to obtain (Bi,Pb)-2223 photosensitive sol.
[0078] At room temperature, a 200 nm thick (Bi, Pb)-2223 photosensitive sol was spin-coated on the upper surface of the LAO (001) single crystal substrate using a coating machine of the Chinese Academy of Sciences at a uniform speed of 4500 r / min for 40 s. That is, a (Bi, Pb)-2223 gel film (such as Figure 1 (as shown in (a)).
[0079] The LAO (001) single crystal substrate with (Bi, Pb)-2223 gel film was placed in an oven and dried at 100 °C for 10 min. A mask with a specific pattern was placed on the upper surface of the (Bi, Pb)-2223 gel film and a light source with a wavelength of 300-375 nm (intensity of 54 mw / cm 2 ) for 45 min (e.g. Figure 1 (b)), and then washed in a polar solvent composed of methanol and acrylic acid (the volume ratio of methanol to acrylic acid is 7:1), so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the LAO (001) single crystal substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the LAO (001) single crystal substrate, so that the (Bi, Pb)-2223 gel film forms a fine pattern with a 10μm microbridge structure, and obtains a (Bi, Pb)-2223 gel film with a fine pattern (as shown in Figure 1 (as shown in (c)).
[0080] The LAO (001) single crystal substrate with a (Bi, Pb)-2223 gel film having a fine pattern was placed in a tube furnace, nitrogen (purity of 99.999%) was introduced into the tube furnace, the temperature of the tube furnace was uniformly increased from room temperature to 135°C at a rate of 6°C / min, and the temperature was kept at 135°C for 20 minutes. Subsequently, a mixed gas composed of water vapor, oxygen and nitrogen (wherein the volume proportion of water vapor is 10%, the volume proportion of oxygen is 5%, the volume proportion of nitrogen is 85%, the purity of oxygen is 99.999%, and the purity of nitrogen is 99.999%) was introduced into the tube furnace, the temperature of the tube furnace was uniformly increased from 135°C to 550°C at a rate of 10°C / min, and the temperature was kept at 550°C for 40 minutes. Finally, a mixed gas consisting of water vapor, oxygen and nitrogen (wherein the volume proportion of oxygen is 5%, the volume proportion of water vapor is 10%, the volume proportion of nitrogen is 85%, the purity of oxygen is 99.999%, and the purity of nitrogen is 99.999%) is introduced into the tube furnace, and the temperature of the tube furnace is uniformly increased from 550°C to 850°C at a rate of 10°C / min, and the temperature is kept at 850°C for 120 minutes. After the insulation is completed, the temperature of the tube furnace is lowered to room temperature, and a patterned (Bi, Pb)-2223 superconducting film (such as Figure 1 (as shown in (d)).
[0081] The thickness of the (Bi, Pb)-2223 superconducting film obtained in Example 1 is 150 nm, and the width of the microbridge is 10 μm.
[0082] Figure 2 This is a confocal plane topography image of the (Bi, Pb)-2223 superconducting film obtained in Example 1. Figure 3 The confocal three-dimensional morphology image of the (Bi, Pb)-2223 superconducting film obtained in Example 1; Figures 2-3 It can be seen that the surface of the micro-pattern is smooth, the edge is flat, and the micro-bridge has no breaks.
[0083] Figure 4 is the UV absorption spectrum of (Bi, Pb)-2223 photosensitive sol obtained by adding photoinitiator TPO; Figure 4 It can be seen that the (Bi, Pb)-2223 gel film has an obvious absorption peak at 365nm, which is consistent with the main band of ultraviolet light wavelength (240-430nm), thus effectively reducing the exposure time.
[0084] Figure 5 The XRD pattern of the (Bi, Pb)-2223 superconducting film obtained in Example 1 is shown in FIG. Figure 5 It can be seen that the (Bi, Pb)-2223 superconducting film obtained in Example 1 contains a symbiotic phase of (Bi, Pb)-2223 and Bi-2212 phases, and the content of the (Bi, Pb)-2223 phase is approximately 65%. Judging from the content of the (Bi, Pb)-2223 phase, the addition of a photoinitiator does not affect the formation of the (Bi, Pb)-2223 phase; furthermore, the main orientation in the figure is (001) c-axis, indicating that the prepared (Bi, Pb)-2223 superconducting film has good consistency in epitaxial growth along the c-axis.
[0085] Figure 6 is the RT diagram of the (Bi, Pb)-2223 superconducting film obtained in Example 1; Figure 6 It can be seen that the superconducting critical transition temperature of the (Bi, Pb)-2223 superconducting film obtained in Example 1 is 108.3K. It can be seen that the preparation method provided by the present invention can effectively maintain the superconducting properties of the (Bi, Pb)-2223 superconducting film.
[0086] Comparative Example 1
[0087] The molar ratio of bismuth ions, lead ions, strontium ions, calcium ions and copper ions was adjusted to 2:0.2:2:1:2, and other conditions were the same as those in Example 1 to prepare a superconducting film.
[0088] Figure 7 is the XRD pattern of the superconducting film obtained in Comparative Example 1. Figure 7It can be seen that only Bi-2212 phase exists in the superconducting film obtained in Comparative Example 1. This is because the Bi-2223 phase is generated by the solid-state reaction of the Bi-2212 phase and some Cu-rich and Ca-rich phases. Therefore, when preparing the sol, it is necessary to increase the two elements of Cu and Ca; and when the molar ratio of bismuth ion, lead ion, strontium ion, calcium ion and copper ion is 2:0.2:2:1:2, it is not rich enough in Cu and Ca, and the (Bi,Pb)-2223 phase cannot be prepared.
[0089] Comparative Example 2
[0090] Under room temperature conditions, bismuth acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:12:20 to obtain a bismuth solution; lead acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:10:20 to obtain a lead solution; strontium acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:15:20 to obtain a strontium solution; calcium acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:15:25 to obtain a calcium solution; copper acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:10:30 to obtain a copper solution.
[0091] The bismuth solution, lead solution, strontium solution, calcium solution and copper solution are stirred and mixed at room temperature, wherein the molar ratio of bismuth ion, lead ion, strontium ion, calcium ion and copper ion is 1.9:0.3:2:2:3, to obtain (Bi,Pb)-2223 sol. Photoinitiator TPO is added to the (Bi,Pb)-2223 sol (the molar ratio of photoinitiator TPO to bismuth ion is 1:8), and stirred at room temperature to obtain (Bi,Pb)-2223 photosensitive sol.
[0092] At room temperature, a 200 nm thick (Bi, Pb)-2223 photosensitive sol was spin-coated on the upper surface of the LAO (001) single crystal substrate using a coating machine from the Chinese Academy of Sciences at a constant speed of 4500 r / min for 40 s, thereby preparing a (Bi, Pb)-2223 gel film on the LAO (001) single crystal substrate.
[0093] The LAO (001) single crystal substrate with (Bi, Pb)-2223 gel film was placed in an oven and dried at 80 °C for 10 min. A mask with a specific pattern was placed on the upper surface of the (Bi, Pb)-2223 gel film and ultraviolet light with a wavelength of 300 to 375 nm (intensity of 54 mw / cm 2) for 10 minutes, and then washed in a polar solvent composed of methanol and acrylic acid (the volume ratio of methanol to acrylic acid is 7:1), so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the LAO (001) single crystal substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the LAO (001) single crystal substrate, so that the (Bi, Pb)-2223 gel film forms a fine pattern with a 10μm microbridge structure, thereby obtaining a (Bi, Pb)-2223 gel film with a fine pattern.
[0094] The LAO (001) single crystal substrate carrying the (Bi, Pb)-2223 gel film with fine patterns was placed in a tube furnace, nitrogen (purity of 99.999%) was introduced into the tube furnace, the temperature of the tube furnace was uniformly increased from room temperature to 125°C at a rate of 5°C / min, and the temperature was kept at 125°C for 20 minutes. Subsequently, a mixed gas composed of water vapor, oxygen and nitrogen (wherein the volume proportion of water vapor is 10%, the volume proportion of oxygen is 5%, the volume proportion of nitrogen is 85%, the purity of oxygen is 99.999%, and the purity of nitrogen is 99.999%) was introduced into the tube furnace, the temperature of the tube furnace was uniformly increased from 125°C to 550°C at a rate of 10°C / min, and the temperature was kept at 550°C for 40 minutes. Finally, a mixed gas consisting of water vapor, oxygen and nitrogen (wherein the volume proportion of water vapor is 10%, the volume proportion of oxygen is 5%, the volume proportion of nitrogen is 85%, the purity of oxygen is 99.999%, and the purity of nitrogen is 99.999%) is introduced into the tube furnace, and the temperature of the tube furnace is uniformly increased from 550°C to 855°C at a rate of 8°C / min, and the temperature is kept at 855°C for 120 minutes. After the insulation is completed, the temperature of the tube furnace is lowered to room temperature, and a (Bi, Pb)-2223 superconducting film is obtained on the upper surface of the LAO (001) single crystal substrate.
[0095] Comparative Example 3
[0096] Under room temperature conditions, bismuth acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:12:20 to obtain a bismuth solution; lead acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:10:20 to obtain a lead solution; strontium acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:15:20 to obtain a strontium solution; calcium acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:15:25 to obtain a calcium solution; copper acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:10:30 to obtain a copper solution.
[0097] The bismuth solution, lead solution, strontium solution, calcium solution and copper solution are stirred and mixed at room temperature, wherein the molar ratio of bismuth ion, lead ion, strontium ion, calcium ion and copper ion is 1.9:0.3:2:2:3, to obtain (Bi,Pb)-2223 sol. A photoinitiator TPO (the molar ratio of photoinitiator TPO to bismuth ion is 1:6) is added to the (Bi,Pb)-2223 sol, and stirred at room temperature to obtain a (Bi,Pb)-2223 photosensitive sol.
[0098] At room temperature, a 200 nm thick (Bi, Pb)-2223 photosensitive sol was spin-coated on the upper surface of the LAO (001) single crystal substrate using a coating machine from the Chinese Academy of Sciences at a constant speed of 4500 r / min for 40 s, thereby preparing a (Bi, Pb)-2223 gel film on the LAO (001) single crystal substrate.
[0099] The LAO (001) single crystal substrate with (Bi, Pb)-2223 gel film was placed in an oven and dried at 90 °C for 10 min. A mask with a specific pattern was placed on the upper surface of the (Bi, Pb)-2223 gel film and ultraviolet light with a wavelength of 300 to 375 nm (intensity of 54 mw / cm 2 ) for 25 minutes, and then washed in a polar solvent composed of methanol and acrylic acid (the volume ratio of methanol to acrylic acid is 7:1), so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the LAO (001) single crystal substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the LAO (001) single crystal substrate, so that the (Bi, Pb)-2223 gel film forms a fine pattern with a 10μm microbridge structure, thereby obtaining a (Bi, Pb)-2223 gel film with a fine pattern.
[0100] The LAO (001) single crystal substrate carrying the (Bi, Pb)-2223 gel film with fine patterns was placed in a tube furnace, nitrogen (purity of 99.999%) was introduced into the tube furnace, the temperature of the tube furnace was uniformly increased from room temperature to 135°C at a rate of 5°C / min, and the temperature was kept at 135°C for 20 minutes. Subsequently, a mixed gas composed of water vapor, oxygen and nitrogen (wherein the volume proportion of water vapor is 10%, the volume proportion of oxygen is 5%, the volume proportion of nitrogen is 85%, the purity of oxygen is 99.999%, and the purity of nitrogen is 99.999%) was introduced into the tube furnace, the temperature of the tube furnace was uniformly increased from 135°C to 550°C at a rate of 10°C / min, and the temperature was kept at 550°C for 40 minutes. Finally, a mixed gas consisting of water vapor, oxygen and nitrogen (wherein the volume proportion of water vapor is 10%, the volume proportion of oxygen is 5%, the volume proportion of nitrogen is 85%, the purity of oxygen is 99.999%, and the purity of nitrogen is 99.999%) is introduced into the tube furnace, and the temperature of the tube furnace is uniformly increased from 550°C to 855°C at a rate of 9°C / min, and the temperature is kept at 855°C for 125 minutes. After the insulation is completed, the temperature of the tube furnace is lowered to room temperature, and a (Bi, Pb)-2223 superconducting film is obtained on the upper surface of the LAO (001) single crystal substrate, wherein the purity of the (Bi, Pb)-2223 superconducting film is 65%.
[0101] Comparative Example 4
[0102] Under room temperature conditions, bismuth acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:12:20 to obtain a bismuth solution; lead acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:10:20 to obtain a lead solution; strontium acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:15:20 to obtain a strontium solution; calcium acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:15:25 to obtain a calcium solution; copper acetate, acrylic acid and methanol are mixed and stirred in a molar ratio of 1:10:30 to obtain a copper solution.
[0103] The bismuth solution, lead solution, strontium solution, calcium solution and copper solution are stirred and mixed at room temperature, wherein the molar ratio of bismuth ion, lead ion, strontium ion, calcium ion and copper ion is 1.9:0.3:2:2:3, to obtain (Bi,Pb)-2223 sol. Photoinitiator TPO is added to the (Bi,Pb)-2223 sol (the molar ratio of photoinitiator TPO to bismuth ion is 1:8), and stirred at room temperature to obtain (Bi,Pb)-2223 photosensitive sol.
[0104] At room temperature, a 200 nm thick (Bi, Pb)-2223 photosensitive sol was spin-coated on the upper surface of the LAO (001) single crystal substrate using a coating machine from the Chinese Academy of Sciences at a constant speed of 4500 r / min for 40 s, thereby preparing a (Bi, Pb)-2223 gel film on the LAO (001) single crystal substrate.
[0105] The LAO (001) single crystal substrate with (Bi, Pb)-2223 gel film was placed in an oven and dried at 100 °C for 10 min. A mask with a specific pattern was placed on the upper surface of the (Bi, Pb)-2223 gel film and a light source with a wavelength of 300-375 nm (intensity of 54 mw / cm 2 ) for 35 minutes, and then washed in a polar solvent composed of methanol and acrylic acid (the volume ratio of methanol to acrylic acid is 7:1), so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the LAO (001) single crystal substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the LAO (001) single crystal substrate, so that the (Bi, Pb)-2223 gel film forms a fine pattern with a 10μm microbridge structure, thereby obtaining a (Bi, Pb)-2223 gel film with a fine pattern.
[0106] The LAO (001) single crystal substrate with a (Bi, Pb)-2223 gel film having a fine pattern was placed in a tube furnace, nitrogen (purity of 99.999%) was introduced into the tube furnace, the temperature of the tube furnace was uniformly increased from room temperature to 135°C at a rate of 6°C / min, and the temperature was kept at 135°C for 20 minutes. Subsequently, a mixed gas composed of water vapor, oxygen and nitrogen (wherein the volume proportion of water vapor is 10%, the volume proportion of oxygen is 5%, the volume proportion of nitrogen is 85%, the purity of oxygen is 99.999%, and the purity of nitrogen is 99.999%) was introduced into the tube furnace, the temperature of the tube furnace was uniformly increased from 135°C to 550°C at a rate of 10°C / min, and the temperature was kept at 550°C for 40 minutes. Finally, a mixed gas consisting of water vapor, oxygen and nitrogen (wherein the volume proportion of water vapor is 10%, the volume proportion of oxygen is 5%, the volume proportion of nitrogen is 85%, the purity of oxygen is 99.999%, and the purity of nitrogen is 99.999%) is introduced into the tube furnace, and the temperature of the tube furnace is uniformly increased from 550°C to 860°C at a rate of 10°C / min, and the temperature is kept at 860°C for 125 minutes. After the insulation is completed, the temperature of the tube furnace is lowered to room temperature, and a (Bi, Pb)-2223 superconducting film is obtained on the upper surface of the LAO (001) single crystal substrate, wherein the purity of the (Bi, Pb)-2223 superconducting film is 65%.
[0107] Figure 8 The morphology of the (Bi, Pb)-2223 gel film with fine patterns obtained by adding the photoinitiator TPO and irradiating it under ultraviolet light for 25 minutes (Comparative Example 3); Fig. 9 The morphology of the (Bi, Pb)-2223 gel film with fine patterns obtained by adding the photoinitiator TPO and irradiating it under ultraviolet light for 35 minutes (Comparative Example 4); Fig.10 The morphology of the (Bi, Pb)-2223 gel film with fine patterns obtained by adding the photoinitiator TPO and irradiating it under ultraviolet light for 45 minutes (Example 1); Figures 8 to 10 It can be seen that the UV irradiation time affects the micro-pattern morphology of the (Bi, Pb)-2223 gel film. Specifically, when the UV irradiation time is 45 minutes, the surface effect of the obtained micro-pattern is the best, with smooth edges and no cracks. When the UV irradiation time is less than 45 minutes, the irradiation time is insufficient, and the polarity distinction between the UV irradiated area and the non-irradiated area is not obvious, resulting in unclear edges of the micro-pattern obtained after dissolution.
[0108] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a (Bi, Pb)-2223 superconducting thin film, characterized in that: The following steps are involved: Bismuth salt, lead salt, strontium salt, calcium salt, copper salt, organic complexing agent, photoinitiator and alcohol solvent are mixed to obtain (Bi, Pb)-2223 photosensitive sol; the (Bi, Pb)-2223 photosensitive sol includes bismuth coordination compound; the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the organic complexing agent includes at least one of organic olefin acid complexing agent and β-diketone complexing agent; The (Bi, Pb)-2223 photosensitive sol is formed into a film on the surface of a substrate by spin coating to obtain a (Bi, Pb)-2223 gel film; The (Bi, Pb)-2223 gel film is irradiated with light under ultraviolet light through a mask plate with a specific pattern, and then washed with a polar solvent composed of methanol and acrylic acid, so that the part of the (Bi, Pb)-2223 photosensitive sol irradiated by ultraviolet light remains on the surface of the substrate, and the remaining (Bi, Pb)-2223 photosensitive sol not irradiated by ultraviolet light is washed away by the polar solvent, exposing the substrate, and obtaining a (Bi, Pb)-2223 gel film with fine patterns; the wavelength of the ultraviolet light used for the light irradiation is 260 to 430 nm; in the polar solvent, the volume ratio of methanol to acrylic acid is 7:1; the structure of the fine pattern is a microbridge structure with a width of 10 μm; The (Bi, Pb)-2223 gel film with fine patterns is subjected to heat treatment to obtain the (Bi, Pb)-2223 superconducting film on the surface of the substrate.
2. The preparation method according to claim 1, characterized in that: The thickness of the (Bi, Pb)-2223 gel film is 200 nm.
3. The preparation method according to claim 1, characterized in that: The light irradiation time is 45 to 60 minutes.
4. The preparation method according to claim 1, characterized in that: The heat treatment includes a first heat treatment, a second heat treatment and a third heat treatment performed sequentially; The first heat treatment is performed in a nitrogen atmosphere; the temperature of the first heat treatment is 100-150° C., the holding time is 20 min, and the heating rate to the temperature of the first heat treatment is 4-10° C. / min; The second heat treatment is performed in a mixed gas atmosphere including water vapor, oxygen and nitrogen; during the second heat treatment, the volume ratio of water vapor, oxygen and nitrogen is 10:5:85; the temperature of the second heat treatment is 550-600°C, the holding time is 30-90min, and the heating rate from the temperature of the first heat treatment to the temperature of the second heat treatment is 10-20°C / min; The third heat treatment is carried out in a mixed gas atmosphere including water vapor, oxygen and nitrogen; during the third heat treatment, the volume ratio of water vapor, oxygen and nitrogen is 10:5:85; the temperature of the third heat treatment is 830-880°C, the insulation time is 60-180min, and the heating rate from the temperature of the second heat treatment to the temperature of the third heat treatment is 8-20°C / min.
5. The preparation method according to claim 1, characterized in that: The mixing comprises the following steps: The bismuth salt, the first part of the organic complexing agent and the alcohol solvent are first mixed in a molar ratio of 1:12-30:20-30 to obtain a bismuth complexing solution; The lead salt, the second part of the organic complexing agent and the alcohol solvent are mixed in a molar ratio of 1:10 to 20:15 to 25 to obtain a lead solution; The strontium salt, the third part of the organic complexing agent and the alcohol solvent are mixed in a molar ratio of 1:15-30:20-30 to obtain a strontium solution; The calcium salt, the fourth part of the organic complexing agent and the alcohol solvent are mixed in a molar ratio of 1:15-30:20-30 to obtain a calcium solution; The copper salt, the remaining organic complexing agent and the alcohol solvent are mixed in a molar ratio of 1:6 to 10:30 to 80 to obtain a copper solution; The bismuth solution, the lead solution, the strontium solution, the calcium solution and the copper solution are mixed for the sixth time and then mixed with the photoinitiator for the seventh time.
6. The preparation method according to claim 1 or 5, characterized in that: The (Bi, Pb)-2223 photosensitive sol includes bismuth ions, lead ions, strontium ions, calcium ions and copper ions; the molar ratio of the bismuth ions, lead ions, strontium ions, calcium ions and copper ions is 1.9:0.3:2:2:
3.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the photoinitiator to the bismuth ion is 1:4-10.
8. The preparation method according to claim 1, characterized in that: The organic olefinic acid complexing agent includes acrylic acid or α-methacrylic acid; the β-diketone complexing agent includes benzoyl acetone.
9. The (Bi, Pb)-2223 superconducting thin film obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the (Bi, Pb)-2223 superconducting film according to claim 9 in superconducting devices.